Oblique waveguide instability in quantum plasmas. (7th October 2020) - Jamil, M; Ilyas, M; Rasheed, A; Ayesha, R; Asif, M; Shahid, M
Abstract: The oblique wave instability is studied extensively in cylindrical bounded quantum plasmas. This study emphasizes on role of quantum features of a plasma system like Fermi degenerate pressure, exchange-correlation potential and Bohm potential as well as the radius of cylindrical geometry on the instability. The growth rate is studied for two cases depending upon the ion gyro time scales. It is found that the growth rate for both cases decreases in a plasma column with the characteristics of wave vector and the parameters like plasma number density, poles of Bessel function and waveguide radius. On increasing these arguments, decreasing of the growth rates respond differently. Numerical analysis of this study is presented on the basis of astrophysical plasma parameters, however, it may be equally useful in the laboratory and discharge plasma technology for some typical set of parameters. Despite the fact of numerous possible applications in technology, the motivation may be extended to the fundamental aspects.